Pelatihan Pembuatan Kain Nusantara Ecoprint dengan Teknik Iron Blanket - Romadhona Chusna Tsani; Afika Yanasikhah; Viky Fitria (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Indonesian Nusantara Fabric is a cultural heritage that has high aesthetic and philosophical value, reflecting the local wealth of various regions. Among the variety of traditional fabrics such as batik, songket, lurik, and ulos, ecoprint fabrics are present as innovations that combine traditional values with sustainability principles. Ecoprints are made using natural materials that are environmentally friendly, making them an alternative to textiles that support nature conservation. One of the techniques used in making ecoprint fabrics is the Iron Blanket technique, which is a coloring method by utilizing a metal reaction to tannins from leaves and flowers. This ecoprint fabric making training is intended for Vocational High School (SMK) students as an educational and cultural preservation effort. The training is carried out through three main stages, namely the preparation stage, the implementation stage, and the evaluation stage. The preparation stage includes the introduction of the concept of archipelago fabric and the principle of ecoprint, while the implementation stage focuses on the direct practice of Iron Blanket techniques. The evaluation stage is carried out to assess students' understanding and skills in producing quality ecoprint fabric works. The purpose of this training is to instill the values of cultural preservation in the younger generation and equip them with creative skills that can be developed independently and in the context of entrepreneurship. The results of the training show that students are able to create ecoprint fabrics with the Iron Blanket technique, understand the sustainable production process, and show enthusiasm in developing local potential. Thus, this training not only contributes to the preservation of the archipelago's fabrics, but also opens up opportunities for the development of cultural-based creative industries among vocational school students.